2016
DOI: 10.1038/nature18632
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mechanisms disrupt the let-7 microRNA family in neuroblastoma

Abstract: Poor prognosis in neuroblastoma is associated with genetic amplification of MYCN. MYCN is itself a target of let-7, a tumor suppressor family of microRNAs implicated in numerous cancers. LIN28B, an inhibitor of let-7 biogenesis, is overexpressed in neuroblastoma and has been reported to regulate MYCN. However, here we show that LIN28B is dispensable in MYCN-amplified neuroblastoma cell lines, despite de-repression of let-7. We further demonstrate that MYCN mRNA levels in amplified disease are exceptionally hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
169
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(177 citation statements)
references
References 58 publications
7
169
0
1
Order By: Relevance
“…It has been shown previously in neuroblastoma that let-7 expression is repressed by the LIN28B protein, which can bind the pri-miR let-7 (among other microRNAs) and prevent their processing into mature, active forms. 3 As a starting point, Powers et al 2 have shown genetically that LIN28B is not required for repression of let-7 function in MYCN-amplified neuroblastoma cell lines. Instead, the abundant MYCN RNA is sufficient to soak up let-7 and still leave enough mRNA to be translated into elevated MYCN protein.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown previously in neuroblastoma that let-7 expression is repressed by the LIN28B protein, which can bind the pri-miR let-7 (among other microRNAs) and prevent their processing into mature, active forms. 3 As a starting point, Powers et al 2 have shown genetically that LIN28B is not required for repression of let-7 function in MYCN-amplified neuroblastoma cell lines. Instead, the abundant MYCN RNA is sufficient to soak up let-7 and still leave enough mRNA to be translated into elevated MYCN protein.…”
mentioning
confidence: 99%
“…Furthermore, the selective pressure in favour of the often extraordinarily high copy number of MYCN genes in neuroblastoma has remained obscure. Now, Powers et al 2 have probably solved the puzzle. The amplification of MYCN copy number produces enough mRNA to effectively titrate down the amount of let-7.…”
mentioning
confidence: 99%
See 3 more Smart Citations